Effect of Plant Products and Containers on Seed Quality during Ambient Storage Conditions in Okra - KP CHAUHAN; GU KULKARNI; LK SHARMA; JB PATEL (Seed Research, 2026)
A laboratory experiment was conducted to study the effect of plant products and containers on seed quality during ambient storage conditions in okra, wherein the seeds of okra cv. GJO 6 were treated with seven plant products (S1 - Control (Untreated); S2 -Trichoderma @5 g/kg of seed; S3 -Sweet flag (Achorusculmus) @10g/ kg of seed; S4 - Castor oil @ 10 ml/kg of seed; S5-Neem oil (10 ml/kg of seed); S6 - Neem powder (5g/kg of seed); S7 - Neem seed kernel extract). Seeds from all treatments were packed in P1- Cloth bag and P2- Aluminium foil bag, and stored under ambient storage conditions of Junagadh. Observations were recorded onseed germination (%), root length (cm), shoot length (cm), seedling length (cm), seedling fresh weight (g), seedling dry weight (mg),seedling vigour index-I, seedling vigour index-II, seed moisture content (%) and electrical conductivity of seed leachates(dS/m) every two months interval until the germination percentage fell below the Indian Minimum Seed Certification Standards (65%).Seeds treated with sweet flag @ 10g/kg seed and stored in aluminium foil bag recorded the maximum germination percentage (95.33%), root length (8.10 cm), shoot length (13.83 cm), seedling fresh weight (288.67 mg), seedling dry weight (28.35 mg) and seedling vigour index II (2702.50) after twelve months of storage.